American constitutionalism heard round the world, 1776-1989 : a global perspective - Billias, George Athan, 1919-2018 (New York : New York University Press, 2016)
George Athan Billias traces the spread of American constitutionalism, from the time of the American Revolution to the conclusion of the Cold War.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Constitutional history -- United States; Constitutional history; Constitutional law -- United States; Constitutional law; World politics -- To 1900.; World politics -- 1900-1945.; World politics -- 1945-1989.; Civilization, Modern -- American influences; Law; United States of America, USA; 18th century, c 1700 to c 1799.; 19th century, c 1800 to c 1899.; 20th century, c 1900 to c 1999.; History